Superparamagnetic iron oxide nanoparticles of curcumin enhance gemcitabine therapeutic response in pancreatic cancer. (July 2019) - Khan, Sheema; Setua, Saini; Kumari, Sonam; Dan, Nirnoy; Massey, Andrew; Hafeez, Bilal Bin; Yallapu, Murali M.; Stiles, Zachary Edwar; Alabkaa, Anas; Yue, Junming; Ganju, Aditya; Behrman, Stephen; et al.
Abstract: Pancreatic cancer is a complex disease accounting for fibrotic tumors and an aggressive phenotype. Gemcitabine (GEM) is used as a standard therapy, which develops chemoresistance leading to poor patient outcome. We have recently developed a superparamagnetic iron oxide nanoparticle (SPION) formulation of curcumin (SP-CUR), which is a nontoxic, bioactive anti-inflammatory/anti-cancer agent for its enhanced delivery in tumors. In this study, we demonstrate that SP-CUR effectively delivers bioactive curcumin to pancreatic tumors, simultaneously enhances GEM uptake and its efficacy. Mechanistic revelations suggest that SP-CUR targets tumor microenvironment via suppression of sonic hedgehog (SHH) pathway and an oncogenic CXCR4/CXCL12 signaling axis that inhibits bidirectional tumor-stromal cells interaction. Increased GEM uptake was observed due to upregulation of the human nucleoside transporter genes (DCK, hCNT) and blocking ribonucleotide reductase subunits (RRM1/RRM2). Additionally, co-treatment of SP-CUR and GEM targets cancer stem cells by regulating pluripotency maintaining stemness factors (Nanog, Sox2, c-Myc and Oct-4), and restricting tumor sphere formation. In an orthotopic mouse model, an enhanced accumulation of SP-CUR was found in pancreas, which potentiated GEM to reduce tumor growth and metastasis. Analysis of tumor tissues suggest that the treatment inhibits tumor stroma (α-SMA, Desmin and Hyluronic Acid) and induces changes in cell stiffness, as measured via Atomic Force Microscopy. This was accompanied by alteration of key cellular proteins of SHH signaling such as SHH, Gli-1, Gli-2, Sufu, and NFĸB-65 as indicated by Immunoblotting and Immunohistochemistry. These results suggest that SP-CUR has a great potential for future clinical use in the management of pancreatic cancer.